Pharmacogenetics in Anesthesia Drugs: A Narrative Literature Review - Ridhuwan, Al Maariz (Open Access Indonesian Journal of Medical Reviews, 2021)
Pharmacogenetics plays an essential role in genetic variations, which are responsible for causing a variable drug response and include the genetic polymorphism of drug transporters, drug-metabolizing enzymes, and drug receptors. This literature review aimed to describe pharmacogenetics in anesthesia drugs. Human gene-disease studies fall into two general classes; linkage studies and association studies, based on the nature of the inheritance pattern. Linkage studies are used in Mendelian disease, often in families with a high prevalence of a single disease observed early in life, in whom multigenerational trees of inheritance of disease can be traced. In conclusion, pharmacogenetics is in the initial stage of clinical practice. Its contribution to new drug development will likely become a reality. Common polymorphisms in drug targets dictate that DNA sequence variations will be considered in the genomic screening processes for new drug development. This will provide new insights for developing medications that target critical pathways in disease pathogenesis and medications that can be used to prevent diseases in individuals genetically predisposed to them.